THE ROLE OF THE ACCOUNTANT IN CONTROLLING FRAUD AND MANIPULATION IN THE ACCOUNTING SYSTEM - Zahraa Naser Ali (Scholar Express Journals, 2025)
The purpose of the research is to illuminate the role of the forensic accountant as an independent variable in reducing the fraud and manipulation of accounting statements as a dependent variable. Ascertaining the purposes in the research required the descriptive approach, given the nature of the research. The research tool was to design a questionnaire that was distributed to a clustering of workers in commercial banks in Basra. The researchers found that the forensic accountant must be familiar with the legal concepts, procedures, and rules, and must identify the legal form and substance with regard to any case with which he works. He should be in judicial commitments to perform an analysis, interpretation, summarization, and presentation of complex subjects clarifying the financial and business merits in an understandable and properly supported manner. One of the most important results reached is that fraud and manipulation of accounting statements are among the most dangerous financial and economic crimes in the current era. The researchers recommend themselves that the forensic accountant should continue at regular intervals to develop his administrative skills by means of endorsements, courses, and training trips to assure that he is well-informed and experienced in explaining and understanding the laws and legal rules in order to identify the suitable material. or legal rule in every case before him
Keywords: forensic accountant; fraud and manipulation of accounting statements; commercial banks